(untitled) (Global Journal of Human-Social Science, 2011)
This article revisits the 2008 general elections in Malaysia to examine how the internet contributed to the remarkable political change never experienced in the history of this country The ruling coalition Barisan Nasional lost its two-thirds parliamentary majority seats it had enjoyed since 1969 while the opposition that ardently utilized the blessings of the internet in the run up to the elections returned to full political limelight The literature examined provides significant leads to the different political scenarios that herald increased internet usage among concerned citizens which we were able to justify against the political reality in Malaysia However through a close study and analysis of Malaysia s political terrain prior to the 2008 general elections we observed that numerous controversial issues and events that engulfed the ruling coalition government which were effectively divulged and most often deliberated upon via the internet infuriated many enfranchised Malaysians hence provided the opposition and civil society activists with tremendous leverage in amassing public support against the ruling coalition This observation leads the article to contend that the degree of contestations contained in a political system and the intensity of information fed unto the internet and regenerated determines the role of the internet as a powerful bridge to political change